OPTIMALISASI MANAJEMEN DESAIN PADA MEDIA KOMUNIKASI WEBSITE UNTUK MENINGKATKAN AKTIVITAS BISNIS - Maulid Agung Triono (Universitas Merdeka Malang, 2019)
Abstract Website management for all companies or organizations is carried out on an basis, and provides a separate space for optimizing the delivery of information, especially relating to products or services. Currently, information and communication technology has become a starting point for managing operational and managerial activities. This will lead to the acquisition of the latest, fast and accurate information in order to support decision making. Basic capital in the realm of information systems that utilize intelligent devices, is an innovation better known as electronic computers set and the internet. When faced with business activities that legalize information disclosure, it is certainly able to provide opportunities for the growth of the communication business and its development by optimizing information technology. This literature study, seeks to dissect the optimization of design management in website communication media as a medium for business improvement. In order to gain an in-depth understanding, efforts were made to bring together a variety of important studies from the dimensions of communication media and business management, in order be able to discover the interconnectedness of various facts in a comprehensive manner. The results of the study illustrate that improving business communication based on technology by utilizing a website, this is inseparable from the concept of the sustainability of an information quality which two point includes: (1) technology exists to achieve the highest level of efficiency in time, human and cost management that demands an adaptive attitude to market fluctuations; (2) management communication perspective puts opportunity as business control, so that the relationships that have been pursued provide positive values ​​in line with the use of the latest communication technology. Keywords: website, design management, business communicationDOI: https://doi.org/10.26905/nomosleca.v5i2.3639